Do women shy away from risky skill games? [Replication package] - Lambrecht, Marco; Oechssler, Joerg (Universität, 2023)
Abstract: A risky skill game is a game in which skill plays an important role but outcomes are also strongly inﬂuenced by random factors. Examples are poker or blackjack but also many economic activities like trading on ﬁnancial markets. In an online experiment we let subjects choose how often they want to play a risky skill game. We ﬁnd that women play only half as many rounds in risky skill games with high variance. In contrast, there is no gender difference if the outcomes depend exclusively on chance or (mostly) on skill. Our results indicate that previous research on gender effects in risky environments (such as tournaments) may have greater applicability than previously thought.